13 rue therese eaudiobook - Shapiro, Elena Mauli (Recorded Books Inc., 2012)
French-born author Elena Mauli Shapiro vividly recreates Paris during World War I in this captivating novel. 13 rue ThErEse follows Trevor Stratton, an American academic working in Paris who discovers a keepsake box dated back to the Great War. The box, Trevor discovers, belonged to a piano teacher named Louise Brunet. Inside it are mementos that give Trevor clues to Louise's life, including the love she lost in the war and her affair with a neighbor. Mesmerized, Trevor begins to imagine what life was like for the mysterious Frenchwoman.